If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-3x=(x/4)
We simplify the equation to the form, which is simple to understand
13-3x=(x/4)
Remove unnecessary parentheses
13-3x=0.25x
We move all terms containing x to the left and all other terms to the right.
-3x-0.25x=-13
We simplify left and right side of the equation.
-3.25x=-13
We divide both sides of the equation by -3.25 to get x.
x=4
| Y-18=-7 | | 2x+5(x-14)=-7 | | 250-4x=85-6x | | 6(5x-9)=186 | | 5X+19X= | | -4(1-5x)=36 | | .714(t+7)=.3t+23 | | 2x+5(4x+4)=262 | | -4x+7-6(x-1)=-(3x-3)-6x+6 | | -11+7=-2(x+9) | | (4x-23)=(3+21) | | 12n^2+11n-36=0 | | .8i+12=.2i+34 | | f(x)=6x^2-5x | | -3b-15=62b+5 | | log(x-2)-6=-2 | | 11x+13+13x-1=180 | | 78m^2+7m+w= | | 3(x+8)+8x=11x-24 | | x^2-4x+y^2+z^2-2z=11 | | 3.1(x+9)+4.3x= | | .857t-12=.214t+15 | | 2x=5(x-3)-11 | | .5v+v^2=-56 | | 0=5y-x-20 | | 3(4x-8)-10x=2(x+4)+8 | | -[4x-(13x+4)]=4+(8x+5) | | 0.4(x-6)=4.8 | | 85+5x+115=180 | | 7z^3+42z^2-189z=0 | | 8(n-3)-15n=11 | | 3y-6=-3(y-2) |